Mesoporous Functionalized Acid Catalysts And Their Use As Environmentally Friendly Catalysts In Esterification Of Glycerols For Monoglyceride Production. - Hermida, L.; Abdullah, A. Z.; Mohamed, A. R. (2008)

(untitled)
Monoglycerides are valuable compounds with wide applications as emulsifiers in food, pharmaceutical and cosmetic industries. They can be produced by esterification of glycerols with fatty acids.